The Outcome of Progressive Uterine Sarcoma with Potential Bone Involvement - Al-Ibraheem, Akram; Abdlkadir, Ahmed S. (World Journal of Nuclear Medicine, 2022)
High-grade endometrial stromal sarcoma (HGESS) is a very rare kind of uterine tumor that accounts for less than 2% of all uterine cancers. The usual sites of metastasis are the abdomen and lung, while bone metastasis is very rare, with only a few cases reported till now. We present a case of HGESS with bone metastasis and review the literature.
Keywords: endometrial stromal sarcoma; uterine sarcoma; bone metastasis; nuclear medicine